2017
DOI: 10.30970/sbi.1101.512
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione antioxidant protection system in ejaculated spermatozoa of infertile men with different forms of pathospermia

Abstract: The level of the products of lipid peroxidation measured as the thiobarbituric acid reactive substances (TBARS) and activity of enzymes of glutathione antioxidant protection system in spermatozoa were studied. It was shown that mean levels of TBARS in sperm cells of infertile men with oligozoo-, astenozoo-, oligoastenozoo-and leucocytospermia were 1.6-, 2.0-, 2.0-and 2.7-fold higher, respectively, compared with such levels in the fertile men. The glutathione peroxidase activity was decreased 2.2-fold in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 17 publications
(23 reference statements)
0
13
0
9
Order By: Relevance
“…The intensity of free radical reactions and processes depends on the concentration of oxygen and the functioning of the enzymatic and nonenzymatic antioxidant systems. In our previous studies (Onufrovych et al, 2016;Fafula et al, 2017) we found depletion of antioxidant systems in particular inhibition of glutathione peroxidase, glutathione reductase and glutathione transferase in spermatozoa of infertile men. Despite the fact that the enzymatic component of the antioxidant protection system is more sensitive to changes in prooxidant-antioxidant balance than nonenzymatic, both systems are closely related.…”
Section: Discussionmentioning
confidence: 78%
“…The intensity of free radical reactions and processes depends on the concentration of oxygen and the functioning of the enzymatic and nonenzymatic antioxidant systems. In our previous studies (Onufrovych et al, 2016;Fafula et al, 2017) we found depletion of antioxidant systems in particular inhibition of glutathione peroxidase, glutathione reductase and glutathione transferase in spermatozoa of infertile men. Despite the fact that the enzymatic component of the antioxidant protection system is more sensitive to changes in prooxidant-antioxidant balance than nonenzymatic, both systems are closely related.…”
Section: Discussionmentioning
confidence: 78%
“…Our former [2][3][4]9] indicate a direction of changes in the biochemical parameters in sperm cells of the infertile men with various forms of semen abnormalities, although it is often a question of combining these forms according to certain criteria. It is known that cluster analysis allows grouping different studied groups at the same values of indices.…”
Section: Resultsmentioning
confidence: 96%
“…Inhibition of ouabainensitive Na + ,K + -ATPase activity in spermatozoa of the infertile men in all forms of pathospermia and decreased activity of tapsigarginsensitive (ERCA) and tapsigargineinsensitive (PMCA) Ca 2+ , Mg 2+ ATPase compared to fertile men was detected. However, Ca 2+ , Mg 2+ ATPase activity tended to an increase in patients with oligozoospermia [9].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations